Pengaruh Investasi, Tingkat Angkatan Kerja, dan Human Capital Investment Terhadap Pertumbuhan Ekonomi Area Pulau Sumatera Perspektif Ekonomi Islam: Analisis Data Panel Tahun 2015-2023 - Apita Sari; Heni Noviarita; Gustika Nurmalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Investment Variables, Labor Force Level, and Human Capital Investment on Economic Growth. With this research, it is hoped that many parties will realize the importance of economic growth in a region and the factors that affect it, so that we can increase economic growth in our respective regions to reduce the gap between regions. This study uses a quantitative research method with analysis of panel data obtained from official publications, such as the Central Statistics Agency and related agencies to measure the magnitude of the influence of the above variables or not. The results of this study show that the Investment Variable has a positive and significant effect on the Economic Growth Variable (GDP). The Labor Force Level (TAK) variable does not have a significant effect on the Economic Growth Variable (GDP). The Human Capital Investment (HCI) variable has a positive and significant effect on the Economic Growth Variable (GDP). Then based on the F-Statistic value of 71,209 with a Prob value (f-Statistic) of 0.000 (<0.05), it can be concluded that the Independent Variable (X) has a significant simultaneous (concurrent) effect on the Dependent Variable (Y)